Copy Number Variation and Frequency of rs179008 in TLR7 Gene Associated with Systemic Lupus Erythematosus in Two Mexican Populations - Guillermo Valencia Pacheco; Yumi E. Nakazawa Ueji; Julián Ramírez Bello; Rosa E. Barbosa Cobos; Eduardo D. Jiménez Becerra; Lizbeth J. González Herrera; Gerardo J. Pérez Mendoza; Nubia A. Rivero Cárdenas; Angélica V. Angulo Ramírez; Ricardo F. López Villanueva (Journal of Immunology Research)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease in which genetic factors play a role in the susceptibility to develop it. Genes related to the synthesis of interferons such as TLR7 and genetics factors such as single nucleotide polymorphisms (SNPs) or copies number variation (CNV) in the gene have been involved with the development of the disease. The genetic differences between the populations contribute to the complexity of LES. Mexico has a mestizo population with a genetic load of at least three origins: Amerindian, Caucasian, and African. The mestizo of Yucatán is the only group whose contribution Amerindian is mainly Mayan, geographically distant from other Mexican Amerindians. We analyzed the CNV and the frequency of SNP rs179008 of the TLR7 as genetic risk factors in developing the disease in patients from Yucatán and Central Mexico. Results show that 14% of the cases of the Yucatecan population showed significantly >2 CNV and a higher risk of developing the disease (OR: 34.364), concerning 4% of those coming from Central Mexico (OR: 10.855). T allele and the A/T and T/T risk genotypes of rs179008 were more frequent in patients of Central Mexico than in those of Yucatán (50% vs. 30%, 93% vs. 30%, 4% vs. 1%), and association with susceptibility to develop SLE was observed (OR: 1.5 vs. 0.58, 9.54 vs. 0.66, 12 vs. 0.14). Data support the genetic differences between and within Mexican mestizo populations and the role of the TLR7 in the pathogenesis of SLE.